Impact of Insulin, Biguanide and Sulfonylurea Treatment on hba1c in Diabetic Patients: An Interventional Study in Rajshahi, Bangladesh (Journal of Bio-Science, 2023)
Proper management and selection of a single drug or multiple drugs for the treatment of diabetes is very important. The choice of treatment depends on a number of factors. With the proper treatment, the state of diabetes can be managed very smoothly. The main objective of this study was to compare the efficacy of insulin, biguanides and sulfonylurea on HbA1C in diabetic patients. This interventional type of study was carried out among 102 diabetic patients attending at different hospitals in Rajshahi of Bangladesh. In this case purposive sampling technique was followed and data revealed that mean age of the patients was 45.98±11.23 years and most of them (35.30) were housewife. Among the insulin receiving group, 41.18% were male and 58.82% were female. In case of the biguanide receiving taking group 44.12% were male and 55.88% were female while for the sulfonylurea receiving group 35.29% were male and 64.71% were female. Regarding body mass index (BMI) among the respondents, it was found that 0.98% had BMI